Bonding characteristics of grouting layer in Prefabricated Cement Concrete Pavement. (1st August 2017) - Zhang, Jun; Weng, Xingzhong; Yang, Bohan; Li, Yifeng; Liu, Junzhong; Jiang, Le
Highlights: Selecting three groutings to study their usability in Prefabricated Pavement. An orthogonal test consisting four factors at three levels has been designed. After fatigue loading, the neutral surface of surface layer has shifted upwards. The grouting material kind is a key factor to properties of pavement structure. Abstract: In order to select an optimum grouting layer to apply to Prefabricated Cement Concrete Pavement, small rectangular-section beam specimens have been used to simulate the airport pavement surface, and the test sections of stabilized soils have been paved indoor as the base layer. An orthogonal test program consisting of four factors (i.e. grouting type, slab bottom roughness, grouting thickness and base structure) at three levels has been designed, in which the vertical static loading, vertical fatigue loading and lateral loading tests have been carried out. The results show that the ordinary cement mortar (PTC) is the most fluid, and the fast setting and hardening cement mortar (SKC) has the highest strength on Day 1 of curing, but its strength increases slowly thereafter. On the other hand, the strength of PTC is the highest on Day 28 of curing. The effect of slab bottom roughness on the bonding performance between the grouting layer and the surface layer is the most significant, while the grouting type has the greatest effect on the bonding performance between the grouting layer and the base layer, and on the bearing capacity of the pavement structure. After the fatigue loading, the neutral surface of the pavement surface layer has shifted upwards. The results show that there are three phases in the relationship between the deflection, pressure and number of fatigue loading times. The first phase is the large change, the second phase is the linear change and the third phase is the constant phase. Under the lateral loading, the bonding performance between the non-shrink grouting material with high strength (CGM) and the base layer is the best, and there is a quadratic polynomial relationship between the lateral load and the superstructure's displacement. When the grouting material is 2.0 cm thick CGM, the bottom of the slab is smooth, and when the basic structure is 12% cement stabilized soil, the pavement structure has the best properties to carry the fatigue load and the lateral load.